Perlindungan Hukum Atas Dikeluarkannya Peraturan Kebijakan (Beleidsregel) - Eric, Eric; Anggraita, Wening (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Policy regulations are not a new phenomenon in governance in Indonesia. Policy regulations arise as a result of the growing needs of the community, which requires the government to take quick legal action, even overriding the principle of legality or what is also known as wetmatigheid van bestuur. Because the authorities have extraordinary powers, administrative law functions to provide legal protection for the people against the actions of the authorities by bringing a lawsuit to the court. Legal protection for the people from government legal action is a juridical means in a rule of law to prevent or restore losses suffered by the people as a result of government legal actions that cause losses to the people.